Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Bantuan Scaffolding Kognitif terhadap Keterampilan Menulis Ilmiah dan Hasil Belajar Siswa SMP dalam Pembelajaran IPA - Arista Eka Kumalasari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
The scientific writing skills and learning outcomes of junior high school students are still at a relatively low level. This condition is influenced by the tendency of teacher-oriented learning. This indicates the need for the implementation of learning models that can encourage student activity and independence in the learning process. This study aims to examine the effect of the application of a guided inquiry learning model combined with cognitive scaffolding on the scientific writing skills and learning outcomes of junior high school students in science subjects. This study used a quantitative approach with a quasi- experimental method and a nonequivalent posttest-only control group design. Sample selection was carried out through a purposive sampling technique, involving two classes, namely the experimental class and the control class. Data processing was carried out through three stages, namely normality testing, homogeneity testing, and hypothesis testing. The results of data analysis showed that the average scientific writing skills and learning outcomes of students in the experimental class were significantly higher than those in the control class. In addition, the results of the hypothesis test showed a significance value of 0.000, which is smaller than the significance level of 0.05 (0.000 < 0.05). Thus, it can be concluded that the application of the guided inquiry learning model combined with cognitive scaffolding assistance has a significant effect on improving the scientific writing skills and learning outcomes of junior high school students.
FINALISASI oleh Arif 2026 Juni 17
Keywords: Scientific writing skills; Learning outcomes; Guided inquiry learning model; Cognitive scaffolding; Science learning